Analysis of User Satisfaction of the Halodoc Telemedicine Platform in DKI Jakarta in 2024 - Ellyamurti, Devanti Octavia; Claudia, Maria; Andini, Tania Meilinda Rizky; Bernarto, Innocentius (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the influence of content, form, and ease of use on user satisfaction of the Halodoc telemedicine platform in DKI Jakarta in 2024. The research method used in this research is quantitative research. they are using the Partial Least Square Structural Equation Modeling (SEM) approach using SmartPLS 3.0 Software. Data was collected using a questionnaire distributed via Google Forms involving 100 respondents. The research results show an influence between content, form, and ease of use on user satisfaction with the Halodoc telemedicine platform in DKI Jakarta in 2024.